A Dual-Identity Model of Responses to Deviance in Online Groups: Integrating Social Identity Theory and Expectancy Violations Theory. Issue 3 (1st November 2017) - Nicholls, Spencer Byron; Rice, Ronald E.
Abstract: Several theories have sought to address responses to normatively deviant behavior, but have done so with a focus either on group-level or on individual-level behavior. Yet, due to some characteristics of online contexts, identities can be salient at both a group and/or individual level, creating a more complex set of influences on responding to deviance. We explore responses to online communicative deviance by integrating social identity approaches (a group-level perspective) and expectancy violations theory (an individual-level perspective). Social identity emphasizes the role of group identification in responding to deviance, especially relevant in anonymous online contexts, while expectancy violations theory notes how individuals respond to ambiguous deviance through assessing the reward value of the deviant.